Soft-chemical synthesis, characterization and humidity sensing behavior of WO3/TiO2 nanopowders - Zanetti, S. M. [UNESP]; Rocha, K. O.; Rodrigues, J. A J; Longo, Elson [UNESP] (Elsevier, 2014)
Tungsten oxide/titania (WO3/TiO2) nanopowders were synthesized by the polymeric precursor method which varied the WO3 content between 0 and 10 mol%. The powders were thermally treated in a conventional furnace and their structural, microstructural and electric properties were evaluated by X-ray diffraction (XRD), Raman spectrometry, N 2 physisorption, NH3 chemisorption, temperature-programmed reduction (TPR), X-ray absorption near-edge spectroscopy (XANES) in situ XANES and extended X-ray absorption fine structure spectroscopy (EXAFS) and transmission electron microscopy (TEM). XRD and Raman spectrometry confirmed the homogeneous distribution of an amorphous WO3 phase in the TiO 2 matrix which stabilized the anatase phase through the generation of [TiO5·V0] or [TiO5·V 0] complex sites. Conventional TPR-H2 (temperature programmed reduction) along with XANES TPR-H2 and XANES TPR-EtOH showed that WO3/TiO2 sample reduction occurs through the formation of these complex clusters. Moreover, the addition of WO3 promoted an increase in the surface acidity of doped samples as revealed by NH3 chemisorption. The WO3/TiO2 bulk-ceramic samples were further used to estimate their potential application in a humidity sensor in the range of 15-85% relative humidity. Probable reasons that lead to the different humidity sensor responses of samples were given based on the structural and surface characterizations. Correlation between the sensing performance of the sensor and its structural features are also discussed. Although all samples responded as a humidity sensor, the W2T sample (2 mol% added WO3) excelled for sensitivity due to the increase in acid sites, optimum mean pore size and pore size distribution. © 2013 Elsevier B.V.
Keywords: Chemical synthesis; EXAFS; Humidity sensor; In situ XANES; Polymeric precursor method; WO3/TiO 2; Extended Xray absorption fine structure (EXAFS) spectroscopies; Polymeric precursor methods; Situ XANES; Structural and surface characterization; Temperature-programmed reduction; X-ray absorption near edge spectroscopy; Chemisorption; Electric properties; Extended X ray absorption fine structure spectroscopy; Humidity sensors; Nanostructured materials; Polymers; Pore size; Spectrometry; Synthesis (chemical); Transmission electron microscopy; X ray diffraction; X ray powder diffraction; Titanium dioxide